2009
DOI: 10.1007/s10157-008-0126-6
|View full text |Cite
|
Sign up to set email alerts
|

Familial hypomagnesemia with hypercalciuria and nephrocalcinosis: unusual clinical associations and novel claudin16 mutation in an Egyptian family

Abstract: The above-mentioned clinical data in the two affected sibs together with the family history of end-stage renal disease associated with nephrocalcinosis and high myopia suggested a diagnosis of FHHNC, which was confirmed for the first time in an Egyptian family by a novel mutation in exon 1 of the CLDN16 gene. Genitourinary associations with FHHNC have not yet been reported in the literature. Here, we will try to highlight the principles of mutation detection based on sequencing with the use of the online NCBI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Although there are no studies focusing on the possible association of primary hypomagnesemia in humans and cataract, indirect evidence from human and animal studies do suggest the possibility of such an association. An association between congenital cataract and a rare autosomal recessive tubular disorder characterized by hypomagnesemia with hypercalciuria and nephrocalcinosis has been reported [20]. Studies have also demonstrated an association of early onset cataract in uncontrolled diabetes and hypomagnesemia [21,22].…”
Section: Association Of Magnesium Deficiency and Cataractmentioning
confidence: 94%
“…Although there are no studies focusing on the possible association of primary hypomagnesemia in humans and cataract, indirect evidence from human and animal studies do suggest the possibility of such an association. An association between congenital cataract and a rare autosomal recessive tubular disorder characterized by hypomagnesemia with hypercalciuria and nephrocalcinosis has been reported [20]. Studies have also demonstrated an association of early onset cataract in uncontrolled diabetes and hypomagnesemia [21,22].…”
Section: Association Of Magnesium Deficiency and Cataractmentioning
confidence: 94%
“…Additional findings include nephrolithiasis, abdominal pain, vomiting, convulsions, muscular twitches, failure to thrive, incomplete distal renal tubular acidosis, and hypocitraturia. 4 The conventional therapy for patients with FHHNC includes magnesium supplements and thiazides to reduce the hypercalciuria, although these medications may improve some biochemical abnormalities, such improvements do not always result in delayed progression of renal dysfunction. 5 Zimmermann et al studied the efficacy of hydrochlorothiazide (HCT) in FHHNC patients in a clinical trial, and concluded that HCT is effective in reducing hypercalciuria due to CLDN16 mutation on a shortterm basis; however, the efficacy of HCT to attenuate disease progression remains to be evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…1 To date, 54 different CLDN16 mutations have been identified, 3 most of these mutations (67%) were missense mutations, although deletions and frameshift mutations were also reported. 4 Here, we describe a novel missense mutation in the CLDN16 gene in a Palestinian family with FHHNC.…”
Section: Introductionmentioning
confidence: 89%
“…The hypothesis of the influence of modulators and epigenetic factors in the clinical spectrum of FHHNC is reinforced by studies that report unusual clinical findings in FHHNC patients with CLDN16 mutations [ 27 29 ] and different clinical courses in siblings with the same CLDN16 mutation [ 17 , 30 ]. One case report presented a boy with a truncating mutation in claudin-16 (p.W237X) with early-onset renal insufficiency, horseshoe kidney, neonatal teeth, atypical face, cardiac abnormalities, umbilical hernia, and hypertrichosis [ 27 ].…”
Section: Case Presentationmentioning
confidence: 99%
“…Another study reported a female patient who experienced recurrent passages of kidney stones and urinary tract infections as of 4 years old, and only developed nephrocalcinosis when she was 19 [ 28 ]. In another case, genitourinary abnormalities (hypospadias and cryptorchidism) were observed in one of the proband’s siblings [ 29 ]. A rare case report described a patient who, in addition to the classical symptoms of FHHNC, was diagnosed with smaller kidneys, severe bone disease, severe metabolic acidosis, and persistent hypocalcemia.…”
Section: Case Presentationmentioning
confidence: 99%